Creativity in fashion design in Slovakia: the case study of Bratislava region - Rudolf Pástor; Jana Parízková (European Regional Science Association (ERSA), 2013)
This paper is focused on creativity in the fashion design in Slovakia. The fashion design in Bratislava region was selected as one of the creative industry for our research. The aim of the paper is to analyze creativity and innovation activities between Slovak fashion designers. In the paper will be presented results from research carried out between Slovak fashion designers located in Bratislava region. The empirical work that provides the basis for this case study used a case study approach and qualitative methodology to discuss development of fashion design in Slovakia and determinants in terms of creativity and innovation activities between Slovak fashion designers. Slovakia has already long tradition in the clothing industry. The continuity in the clothing production was interrupted, with the closure of former state clothing factories. Also fashion design in Slovakia has overcome interesting development together with economic and social transformation in the 1990s. We will draw our attention also to history of fashion design in Slovakia. More in detail we anaåyze the value added chain of Slovak fashion producers, cooperation between fashion designers in Bratislava region, relationship with their main suppliers and customers, markets etc. The paper examines also recent state of the impact of global economic crisis on the fashion industry in Slovakia. Creative industries generally and fashion design as well has clear tendency to localize in the big or capital cities ? ?fashion centres? or ?fashion cities?. Bratislava as the most important Slovak fashion centre has also attracted the famous fashion designers from other Slovak regions. These fashion designers are leaders on the Slovak fashion scene and they have succeeded with their own original fashion collection regularly presented on the fashion shows.
Keywords: L67; Z10; 330; creative industry; fashion; fashion design